2021
DOI: 10.1101/2021.02.12.430987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SalmonellaTyphimurium outer membrane protein A (OmpA) renders protection against nitrosative stress by promoting SCV stability in murine macrophages

Abstract: Porins are highly conserved bacterial outer membrane proteins having β barrel structure and are majorly involved in the selective transport of charged molecules across the membrane. Despite having huge contributions in the pathogenesis of many gram-negative bacteria, their role remains elusive in salmonellosis. In this study, we have characterized the pathogenic role of porins majorly found on the outer membrane of Salmonella Typhimurium (such as OmpA, OmpC, OmpD, and OmpF) paying the utmost importance to OmpA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 80 publications
(181 reference statements)
2
8
0
Order By: Relevance
“…Earlier, our group has shown that this cytosolic population of the bacteria becomes hyper-proliferative inside the epithelial cells, and their intracellular proliferation was significantly attenuated in macrophages. Our study further depicted that STM ΔompA is unable to recruit T3SS2 translocon proteins (SseC and SseD) on its surface and is deficient in producing an SPI-2 effector [15]. Available literature suggests that Salmonella deficient in making active T3SS2 and with damaged SCV cannot suppress host autophagy machinery.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Earlier, our group has shown that this cytosolic population of the bacteria becomes hyper-proliferative inside the epithelial cells, and their intracellular proliferation was significantly attenuated in macrophages. Our study further depicted that STM ΔompA is unable to recruit T3SS2 translocon proteins (SseC and SseD) on its surface and is deficient in producing an SPI-2 effector [15]. Available literature suggests that Salmonella deficient in making active T3SS2 and with damaged SCV cannot suppress host autophagy machinery.…”
Section: Discussionsupporting
confidence: 61%
“…Earlier, we have shown an enhanced expression of ompA transcript in wild type Salmonella Typhimurium growing intracellularly in murine macrophages at 9 th and 12 th hours postinfection, which suggested the requirement of OmpA for the intracellular survival of bacteria [15]. Our current study revealed that in the absence of OmpA, Salmonella cannot stay inside SCV and comes into the cytosol of host cells.…”
Section: Salmonella Typhimurium Ompa Plays a Critical Role In Maintaining Host Lamp-1 (Scv) Interaction During Infection In Macrophagessupporting
confidence: 60%
See 3 more Smart Citations